Trends of research on women's entrepreneurship on the management of happiness and well-being in organisations - De-las-Heras-Pedrosa, Carlos; Jambrino-Maldonado, Carmen; Rando-Cueto, Dolores; Iglesias-Sánchez, Patricia Pilar (Emerald, 2023)
Purpose The management of employee happiness and well-being has been gaining interest in academic research in recent years; however, few studies have focussed on the entrepreneur's perspective. The aim of this paper is to analyse the state of research on women-led businesses, well-being and happiness management. Design/methodology/approach A bibliometric study has been carried out since 1996, the first year in which publications in this field were detected. In total, 128 papers are identified in the most reliable database, Web of Science Core Collection. A network mapping of authorship, citation and co-occurrence of keywords in scientific publications is shown. Findings The results of this study confirm that societal changes resulting from crises increase research interest in improving organisational environments and happiness. After the economic crises of 2013, there was a boost, and after the pandemic, there is again a boost in research. More than half of the publications and citations on female entrepreneurship and happiness management are post-pandemic. The study offers some research directions and emphasises the role of gender. Originality/value This article brings a new approach to the study of well-being in organisations, highlighting the relevance of the role female leadership plays in promoting happiness at work.
Keywords: Mujeres; Bienestar social; Entrepreneurship; Women; Happiness; Well-being; Wellness; Bibliometric analysis; Scientometric analysis